2000
DOI: 10.1161/01.hyp.36.4.642
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Prevents Changes in Nitric Oxide Synthase mRNA Levels Induced by Cyclosporine

Abstract: Abstract-Cyclosporine toxicity mainly affects kidney and liver function. We have previously shown that cyclosporine nephrotoxicity alters kidney nitric oxide synthase mRNA pattern of expression. To determine if nitric oxide synthase expression changes are mediated directly by cyclosporine or by secondary hemodynamic alterations induced by cyclosporine, we evaluated if these effects are tissue specific and if nifedipine-induced vasodilation prevents these alterations. Uninephrectomized Wistar rats treated for 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Sanchez-Lozada et al showed that NF prevented declines in renal function in CsA-treated rats, with no interference in the expression of NOS isoforms. This suggests that the changes in the NOS isoform pattern of expression induced by CsA appear to be, at least in part, mediated by the haemodynamic alterations induced by this drug [22]. Travis et al showed that the vasodilator responses elicited by systemic injections of NO donors were markedly attenuated by NF, suggesting that NO relaxes resistance arteries 'in vitro' by inhibition of Ca 2+ channels [23].…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez-Lozada et al showed that NF prevented declines in renal function in CsA-treated rats, with no interference in the expression of NOS isoforms. This suggests that the changes in the NOS isoform pattern of expression induced by CsA appear to be, at least in part, mediated by the haemodynamic alterations induced by this drug [22]. Travis et al showed that the vasodilator responses elicited by systemic injections of NO donors were markedly attenuated by NF, suggesting that NO relaxes resistance arteries 'in vitro' by inhibition of Ca 2+ channels [23].…”
Section: Discussionmentioning
confidence: 99%
“…53,54 It has also been proven to reduce cyclosporine-induced hyperreactivity of vascular smooth muscle to catecholamines and to reverse its negative effect on NO synthase activity in the kidney core. 14,55 However, it should be remembered that nondihydropyridine CCB (ie, verapamil and diltiazem) increase CsA and TAC by inhibiting CYP3A4. 56 Other antihypertensive drugs have also been studied in renal transplant patients with good results.…”
Section: Concepts Of Treatment Of Ht Caused By Immunosuppressive Drugsmentioning
confidence: 99%
“…After the administration of CsA, an increase in the expression of endothelial nitric oxide synthase (eNOS) was detected at both the RNA and the protein level in the renal cortex in rats (Bobadilla et al 1998 andSanchez-Lozada et al 2000). After the administration of CsA, an increase in the expression of endothelial nitric oxide synthase (eNOS) was detected at both the RNA and the protein level in the renal cortex in rats (Bobadilla et al 1998 andSanchez-Lozada et al 2000).…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%